2022
DOI: 10.1038/s41380-022-01436-7
|View full text |Cite
|
Sign up to set email alerts
|

Age, sex and APOE-ε4 modify the balance between soluble and fibrillar β-amyloid in non-demented individuals: topographical patterns across two independent cohorts

Abstract: Amyloid (Aβ) pathology is the earliest detectable pathophysiological event along the Alzheimer’s continuum, which can be measured both in the cerebrospinal fluid (CSF) and by Positron Emission Tomography (PET). Yet, these biomarkers identify two distinct Aβ pools, reflecting the clearance of soluble Aβ as opposed to the presence of Aβ fibrils in the brain. An open question is whether risk factors known to increase Alzheimer’s’ disease (AD) prevalence may promote an imbalance between soluble and deposited Aβ. U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Indeed, a study by Cacciaglia et al . 65 recently showed that age, APOE ɛ4 and female sex were associated with higher amyloid-PET uptake in posterior middle cortical regions in cognitively unimpaired individuals. Likewise, APOE ɛ4 carriers in both sexes tended to show lower cerebral glucose metabolism compared with non-carriers, although the sample size of the subgroups was small to compare by sex.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a study by Cacciaglia et al . 65 recently showed that age, APOE ɛ4 and female sex were associated with higher amyloid-PET uptake in posterior middle cortical regions in cognitively unimpaired individuals. Likewise, APOE ɛ4 carriers in both sexes tended to show lower cerebral glucose metabolism compared with non-carriers, although the sample size of the subgroups was small to compare by sex.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the temporal lobe, a recent study on the sample included here showed that APOE-ε4 carriers were more prone to Aβ aggregation in temporal areas for any given level of soluble Aβ dyshomeostasis. This finding suggests that APOE-ε4 facilitates the spread of Aβ in these regions, promoting an earlier co-localization with tau [ 42 ] to trigger AD-related neurodegeneration. Taken together, these studies suggest an interplay between patterns of Aβ and tau spread in determining cognitive decline, which would explain why positivity in regions of late Aβ accumulation is associated with cognitive decline in APOE-ε4 carriers in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed, as suggested in previous studies, that reversed the association between cognitive performance and brain morphology, similar to aging, suggesting that this risk allele leads to an accelerated biological phenotype of brain aging (Cacciaglia et al, 2019). Furthermore, ε4-homozygotes displayed reduced connectivity between networks in areas typically susceptible to amyloid deposition in the early AD continuum, and altered effects of amyloid on brain structure (Cacciaglia et al, 2020(Cacciaglia et al, , 2022.…”
Section: Background: Initial Progress In Genetic Research Within the ...mentioning
confidence: 99%